A flexible flux adjustable variable flux leakage starter‐generator for helicopters - Hainiu Chen; Shuhua Fang; Ling Qin; Yicheng Wang; Qiangren Xu (IET Electric Power Applications)
Abstract A variable flux leakage starter‐generator structure designed for helicopters is proposed. The research focuses on investigating the current distribution mechanism of the d‐q axis to determine the feasibility of incorporating variable flux leakage (FL) in the machine model. By investigating the magnetic circuit models of machines under various operating conditions, we aim to uncover the performance advantages of variable FL starter‐generator for helicopters in different scenarios. Subsequently, a variable flux leakage starter‐generator is designed, and a prototype is implemented successfully. The experimental results validate the accuracy of the theoretical analysis conducted.